Diversion in the Child Criminal Justice System as an Effort to Implement Restorative Justice - Dewi Setyowati (Faculty of Law, University of Mataram, 2020)
The juvenile criminal justice system according to Article 1 of Law Number 11 Year 2012 concerning the Criminal Justice System for Children (hereinafter referred to as SPPA Law) is the whole process of resolving cases of children in conflict with the Law from the investigation stage to the guidance stage after undergoing a crime. The application of SPPA involves many parties consisting of the police, prosecutors, legal advisors, courts, and correctional institutions, and child development. One of the law enforcers (structures) in SPPA that has a significant role is the prosecutor's office. The Prosecutor's Office as the prosecuting body that has been given the authority to solve the problems of children in conflict with the Law (hereinafter referred to as ABH) by using diversion to realize Restorative Justice, as stipulated in the provisions of Article 7 Paragraph 1 of the SPPA Law. What if, in this stage, the diversion was not sought for ABH? What is the form of violations experienced by ABH in the criminal justice system, especially at the prosecution stage? The method used is legal/normative research based on laws and regulations relating to one another. The Indonesian Attorney's Office in the constitutional system, as a body related to judicial authority, with a very dominant function as the dominus litis principle, controls the case process that determines whether a person can be declared a defendant and is submitted to the Court based on legal evidence according to the Law, and as ambtenaar executive implementing the decision and court decisions in criminal cases. The SPPA Law material test is a struggle in the context of maintaining the constitutional rights of law enforcers in their duty and is not intended to reject diversion in handling ABH. This provision is related to the protection of the law enforcement profession guaranteed by the constitution. Even though the Supreme Court has declared article 96 of the SPPA Law being applied unconstitutional or revoked, it does not mean allowing law enforcers the police, judges, and prosecutors not to carry out diversion obligations.